Critical design issues of retrofit light-emitting diode (LED) light bulb - Li,S; Chen,H; Tan,SC; Hui,SYR; Waffenschmidt,E (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2014)
For retrofit applications, some high-brightness (HB) light-emitting diode (LED) products have the same form factor restrictions as existing light bulbs. Such form factor constraints may restrict the design and optimal performance of the LED technology. In this paper, some critical design issues for a commercial LED bulb designed for replacing an E27 incandescent lamp are quantitatively analyzed. The analysis involves a power audit on such densely packed LED system so that the amounts of power consumption in (1) the LED driver, (2) the LED wafer, (3) the phosphor coating, and (4) the bulb translucent cover are quantified. The outcomes of such an audit enable R&D engineers to identify the critical areas that need further improvements in a compact LED bulb design. © 2014 IEEE.